Learning from the environment: how predation changes the behavior of terrestrial Isopoda (Crustacea Oniscidea). Issue 1 (2nd January 2020) - Cazzolla Gatti, Roberto; Messina, Giuseppina; Tiralongo, Francesco; Ursino, Lorenzo A.; Lombardo, Bianca M.
Abstract : Terrestrial isopods have adapted to predatory pressures by evolving a variety of behaviors, which arise from a combination of specific traits, such as volvation and tonic immobility. Evolutionarily, these behavioral adaptations have been shown to increase the fitness of the individuals of the species who show them because the probability of being predated is reduced due to the loss of interest by the predator towards the immobile prey and the increase of interest towards the other mobile ones. Even if some of these behaviors have been shown to have a genetic basis, there is limited knowledge about the effects of environmental influences and predator-induced learning abilities on the antipredatory strategies of invertebrates, and isopods in particular. Our study aimed to understand the degree to which "nature" and "nurture" (i.e. environmental and genetic factors) and their interactions influence these antipredatory behaviors. There might be a difference in the behavior of wild and captive isopods in their volvation frequency and duration of tonic immobility due to environmental factors (i.e. predation) that induce learning-related behavioral changes. Therefore, we tested this hypothesis. We applied the three types of stimuli, which aim to simulate the interaction of the predator with the isopod. All three species showed a significant difference, between individuals collected in the field (wild) and raised in the laboratory (captive), in the reaction to the stimulus that simulates the fall from a bird's beak or from the jaws of a lizard after a catch. Although volvation frequency was highly species- and stimulus-specific, the duration of tonic immobility and the delay in the response to each stimulus, when significant, was always higher in wild groups than captive ones. These substantial differences may reflect the evolutionary and ecological characteristics of each species and the importance of environmental pressures to shape the behavior of these invertebrates to optimize their life strategies.